Adolf Hitler, existence and his political victim until junuary, 1933 Dr.Suaad Rood Sheer Mohammed (PhD) Dr. Qassim Abdul Amir Waseem (Journal of the College of Education for Women, 2017)
This study aims to track and analysis Hitler's personality by explaining the impact of the social environment in shaping his behavior and addressing the defeat of Germany in the World War 1 and its impact on building his political personality and included his political activism and his policy to get rid of the terms of the Versailles Military Treaty in the light of his plans in his book ( Kifahi) The nature of the study had to be divided into an introduction and two topics followed by the conclusion of the most important results, in addition to a list of references and a summary in English and from God the Good luck.